Associations Between Digital Lifestyle, Social Factors, and Adolescent Obesity: A Case-Control Study in Tasikmalaya Regency, Indonesia - Muharry, Andy; Siti Aisyah, Iseu; Yogaswara, Dadan (Media Publikasi Cendekia Indonesia, 2025)
The rising prevalence of overweight and obesity today is associated with various factors, including digital behaviors and the social environment. This study examines the relationships between screen time, sleep duration, attitudes, physical activity, average gaming time, and the number of gaming peers with the incidence of obesity among adolescents. This study is a matched case-control study design. The study population comprises adolescents aged 16–18, encompassing both case and control groups. The case population includes adolescents with obesity in Leuwisari District, while the control population comprises non-obese adolescents from the same location. Case samples were determined based on data from the AUSREM Program, identifying 42 obese adolescents. Meanwhile, the control sample consists of non-obese adolescents selected purposively with a 1:1 matching ratio to the case group, ensuring comparable characteristics. Consequently, the total sample size for this study amounts to 84 participants. Data collection was conducted through questionnaires. Data analysis for screen time, sleep duration, attitudes, and physical activity used the McNemar test. Meanwhile, Pearson correlation was applied to measure the correlation between average gaming time and the number of gaming friends. The results indicate that variables significantly associated with adolescent obesity include screen time (OR=6.33, p=0.000), sleep duration (OR=4.25, p=0.004), Adolescents' attitudes toward obesity (OR=8.17, p=0.004), physical activity (OR=6.00, p=0.004), average gaming time (r=0.624, p = 0.012), and number of gaming friends (r=0.509, p = 0.000).